IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN SCAFFOLDING PADA PEMBELAJARAN IPA KELAS III MATERI WUJUD BENDA DI SDN POLISI 2 BOGOR - Alya Adenia; Mursidah Rahmah; Riksa Suci Imaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the implementation of Problem Based Learning model with Scaffolding in class III science learning material in the form of objects at SDN Polisi 2 Bogor. The research method used is descriptive qualitative with data collection techniques which include interviews, observations and documentation. The results showed that learning science class III material in the form of objects that implement the Problem Based Learning model with Scaffolding can attract student learning motivation and increase student curiosity. Deep and meaningful learning can be created through Problem Based Learning because it involves students in direct problem solving with the help of scaffolding from teachers or peers. So that the Problem Based Learning model can provide more depth and meaning for students.